Estudo da proteção de ácidos graxos de cadeia longa presentes em subproduto da agroindústria visando aplicação em nutrição animal - Fujieda, Roberto Joanne Yoshihiro (Universidade Federal de São Carlos, 2012)
Ruminant diets are characterized by low levels of lipids and these may be supplied by different sources, such as by-products of oil industries. The soapstock is the main by-product of the vegetable oils refining industry. To make use of this by-product in ruminant diets, aiming for a efficient result, the fatty acids must be protected. The protected fat is a source of unsaturated fat wich reacts with calcium to form a salt widely known as calcium soap. The present research evaluated the content and fatty acid composition by gas chromatography and also the concentration of the following analytes: Na, Ca, K, Mg, P, S, Fe, Zn, Mn, As, Cd, Co, Hg, Pb, Se and Cu (ICP OES), in four different origins of lees (A Soybeans soapstock, C Soybeans soapstock, B cotton sead soapstock and D flaxseed soapstock). The logistics was also considered for selection of the material, once it is extremely important in assessing the costs/benefits of the best lees source. To evaluate the process of fat protection it was applied the factorial design (24 e 22), and the final product was characterized by the same parameters of the raw. The lipid content for the four samples was approximately 51%. The fatty acid composition relative to oleic, linoleic and linolenic acids proved to be more favorable to the lees of A, C and D. The content of As, Cd, Co and Pb of the four samples of soapstock were below the LOD. Therefore, logistics was was determinant for the choice of A soapstock. Total fat content and fatty acids composition did not change significantly when compared with the raw material. It is possible to scale-up the process. The evaluation of costs for the fat protection process showed that about 93% more viable than the commercial protected fatty acids. It follows that the lees chosen presented high potential for the required use.
Protection of long chain fatty acids present in by-products of agro industries aiming at animal nutrition.
Keywords: Química analítica; Óleos e gorduras - processamento; Ruminantes; Nutrição animal; Ácidos graxos; CIENCIAS EXATAS E DA TERRA::QUIMICA